Sheath-tailed bats (Chiroptera: Emballonuridae) from the early Pleistocene Rackham’s Roost Site, Riversleigh World Heritage Area, and the distribution of northern Australian emballonurid species - Tyler R. King; Troy J. Myers; Kyle N. Armstrong; Michael Archer; Suzanne J. Hand (PeerJ, 2021)
Sheath-tailed bats (Family Emballonuridae) from the early Pleistocene Rackham’s Roost Site cave deposit in the Riversleigh World Heritage Area, north-western Queensland are the oldest recorded occurrence for the family in Australia. The fossil remains consist of maxillary and dentary fragments, as well as isolated teeth, but until now their precise identity has not been assessed. Our study indicates that at least three taxa are represented, and these are distinguished from other Australian emballonurids based on morphometric analysis of craniodental features. Most of the Rackham’s Roost Site emballonurid remains are referrable to the modern species Taphozous georgianus Thomas, 1915, but the extant species T. troughtoni Tate, 1952 also appears to be present, as well as a very large, as-yet undetermined species of Saccolaimus Temminck, 1838. We identify craniodental features that clearly distinguish T. georgianus from the externally very similar T. troughtoni. Results suggest that the distributions of T. georgianus and T. troughtoni may have overlapped in north-western Queensland since at least the early Pleistocene.